Comparative study of doped ceria thin-film electrolytes prepared by wet powder spraying with powder synthesized via two techniques - Shi, H.; Zhou, W.; Ran, R.; Shao, Zongping (Elsevier SA, 2010)
Fabrication of dense Sm0.2Ce0.8O1.9 (SDC) thin-film electrolytes by wet powder spraying in combination with high-temperature sintering is investigated. Two powder synthesis techniques, i.e., a hydrothermal synthesis and an EDTA-citrate complexing sol-gel process, were investigated. X-ray diffraction, BET surface area and laser particle size analysis demonstrate there is certain level of aggregation in both powders. However, it is more pronounced in powders obtained by the complexing process, and only the colloidal suspensions of powders prepared by hydrothermal synthesis are stable. SEM analysis of the green and sintered thin-film electrolytes demonstrate that the SDC electrolyte with powders prepared via the hydrothermal synthesis is denser. By optimizing the fabrication conditions, dense SDC electrolytes with a thickness of ~12 µm are successfully fabricated. The cells with SDC prepared from hydrothermal synthesis demonstrate open circuit voltages and power outputs similar to those of similar cells fabricated from other advanced techniques. Because of its simplicity and flexibility for anode substrate geometric shape, it turns out to be a promising technology to fabricate thin-film SDC electrolyte for solid-oxide fuel cell application. © 2009 Elsevier B.V. All rights reserved.